Evaluation of antivenom therapy for Vipera palaestinae bites in children: experience of two large, tertiary care pediatric hospitals. (21st April 2017) - Pivko-Levy, Dikla; Munchnak, Itamar; Rimon, Ayelet; Balla, Uri; Scolnik, Dennis; Hoyte, Christopher; Voliovitch, Yair; Glatstein, Miguel
Abstract: Background: Antivenom has been successfully used to treat systemic and progressive, local manifestations of envenomation inflicted by Vipera (V.) palaestinae, the most common venomous snake in Israel. The objective of this study was to evaluate the fixed dose V. palaestinae monovalent (equine) immunoglobulin G antivenom used in two pediatric emergency departments. In particular, we wanted to assess the need for repeated antivenom administration and the rate of adverse antivenom effects in children. Methods: A retrospective chart review was performed for all children admitted with definite or probable signs of V. palaestinae envenomation to Chaim Sheba Medical Center and Kaplan Medical Center between 1 March 2008 and 1 March 2014. Extracted data included: age, location of bite, time to hospital arrival, time to antivenom administration if indicated, outcomes, and complications of the envenomation and adverse effects to the antivenom. Results: 57 patients met inclusion criteria; they ranged from 1 to 17 years in age and median age was 9.5 years. Clinical manifestations were evident in 55 (96.4%) of victims: 18 presented with minimal local signs and 37 showed marked progressive, local features (rapidly progressing edema) and signs of systemic envenomation: tachycardia (20), vomiting (17), abdominal pain (11) and hypotension (6). Two patients developed compartment syndrome and underwent surgical decompression (both received only a loading dose of antivenom with no subsequent maintenance dose). One patient developed thrombocytopenia and three patients presented with mild coagulopathy. Antivenom was administered to 25 (42%) children. Indications for antivenom administration included moderate to severe local signs (19 patients) and systemic signs (6 patients). None of these patients developed adverse reactions, serum sickness, or other side effects to the antivenom. One patient received a single additional 30mL dose of antivenom, due to hypotension and syncope, with good response. Conclusions: In children, 50 ml dosing of V. palaestinae antivenom is efficacious and safe for the treatment of systemic and progressive local manifestations of envenomation by V. palaestinae .